Pengaruh Penerapan Model Pembelajaran Cooperative Learning Tipe Student Teams Achievement Divisions (STAD) Terhadap Keaktifan Belajar PAI Siswa Di SMP N 2 Kamang Magek - Maisyarah Mardhatillah; Arifmiboy Arifmiboy; Darul Ilmi; Deswalantri Deswalantri (Universitas Maritim AMNI Semarang, 2023)
The research was conducted on the basis of the level of student learning activeness in PAI learning which is still low. So the purpose of this study is to determine the effect of the implementation of the STAD learning model on student learning activeness and the difference with using conventional models. This research is an experimental research with The Static Comparison design. The research sample of VIII grade students at SMP N 2 Kamang Magek was randomly selected with a total sample of 44 students. The research sample was class VIII.I as a control class with a conventional model and class VIII.II as an experimental class with the STAD model. The data collection techniques using SPSS, normality test with the Shapiro Wilk test, and homogeneity test with the Levene test, and condtinued with hypothesis testing ith the One Sample T test. The results of research and data processing prove that there is an influence of the STAD mdl on learning activity as evidemced by Sig. (2-tailed) =.000 <0.05 with the research alpha value = 5% or 0.05. which means that the significance value is greater than the alpha value. So significantly Ha is accepted and H0 is rejected. As well as the calculated T value of 7.060> T table 1.721. So that based on the comparison of T values, Ha is accepted and H0 is rejected.